Analysis Of Factors Affecting Musculoskeletal Disorders (MSDs) On Nurses At Nunukan Regional General Hospital - Musdalifah, Aida Ummul Ainun; Thamrin, Yahya; Amiruddin, Ridwan; S Russeng, Syamsiar; Wahyu, Atjo; Wahyu, Atjo; Salma, Ummu (Journal of Neonatal Surgery, 2025)
Background. Musculoskeletal disorders (MSDs) are disorders of the muscoleskeletal system including muscles, tendons, ligaments, nerves, joints and bones. Factors that affect MSDs are age, BMI, work period, workload and fatigue. Aims. This study is to analyze the relationship between age, BMI, tenure, workload and fatigue to the occurrence of MSDs complaints in nurses at RSUD Nunukan. Methods. This study used a cross-sectional design with a quantitative approach. The study sample consisted of 150 nurses selected using simple random sampling technique. Data were collected through Nordic Body Map (NBM) questionnaire to measure MSDs complaints, as well as NASA-TLX and KAUPK2 questionnaires to measure mental workload and job fatigue. Data were analyzed using chi-square test and logistic regression. Results. The results showed that there was a significant relationship between BMI (p=0.027), length of service (p=0.035), physical workload (p=0.018), mental workload (p=0.039) and job fatigue (p=0.028) with the incidence of MSDs in nurses. The age factor (p=0.498) did not have a significant relationship with MSDs. Conclusion. BMI, length of service, physical workload, mental workload and job fatigue are factors that influence the incidence of MSDs in nurses at RSUD Nunukan. Preventive efforts such as the implementation of work ergonomics, workload management, and physical health promotion need to be improved to reduce MSDs complaints among nurses.